幼兒科學創造力評量方法之發展：嵌入式評量設計 The Technique Development of Assessing Preschool Children's Creativity in Science: An Embedded Assessment Design - 侯雅齡 Ya-Ling Hou (National Taiwan Normal University, 2009)
本研究主要目的在於發展幼兒科學創造力評量方法。研究者首先設計能啟發幼兒創造力的科學課程，藉由蒐集幼兒於課程中的創造力表現作為工具發展的參考，最後則擴大參與對象，取得評量工具在計量基礎上的信、效度證據。研究參與者為三百零八位幼稚園大班的幼兒。本研究所發展的課程，包含五個動手做物理活動，各活動又分探索、鷹架支持與成果展現三階段來進行，以啟發幼兒的科學創造力。二份評量表，分別為瞭解幼兒在科學活動中運用問題解決技巧的幼兒科學創造力評量表；以及在活動歷程展現愉悅的態度、專注力、投入其中願意接受挑戰和充滿好奇的幼兒心流經驗量表。兩份量表的全量表內部一致性信度為 .955與 .905，驗證性因素分析結果理論與觀察資料間有良好的適配性，表示量表有良好的信度與建構效度。 The purpose of this study was to develop preschool children's creativity assessment in science, including The Preschool Children's Science Creativity Scale (PCSCS) and The Preschool Children's Science Flow Experience Scale (PCSFES). The researcher designed 5 hands-on Physics activities and 3 periods instruction designed under the framework of exploration, scaffolding and show as creative curriculum. 308 children sampled from 8 kindergartens participated in this study. The results have shown: (1) The PCSCS and The PCSFES have reached satisfactory level of internal consistency reliability and inter-rater reliability. In two scales Cronbach α coefficients were .955 and .905. (2) By using confirmatory factor analysis to examine the model, the researcher found the model fit indices indicated that PCSCS and PCSFES fitted the observed data. The construct-related validity was found satisfactory.